STUDI POTENSI LANSKAP SEJARAH UNTUK PENGEMBANGAN WISATA SEJARAH DI KOTA BOGOR - Ira Puspa Kencana; Nurhayati HS Arifin (Jurnal Lanskap Indonesia, 2010)
Bogor has main role in Sundanese history, so there  are many historical heritages which are needed to be conserved. One of the effortis tourism development. The research was conducted to analize historical landscape potency for developing historical tourism. The study was held in Bogor city from December 2004 until May 2005 using survey method. The survey method were todefine the historical data of the city, historical object and management.The study explains the historical landscape potencyin Bogor city as an historical tourism object for historical tourism development.  Based on Bogor tourism, art, and culture office recommendation, there are six historical objects that have tourism potency. Some of those objects are needed to be rehabilited and conserved. Tourism supporting aspects such as services facilities and  tourism have good potency. Transportation still has problem that need to be solved. Beside that, information of Bogor history and its historical tourism objects are necessary to be socialized and promoted. Tourism program is one of the recommendedsolution.